A new genus of Stigmaeidae (Acari: Prostigmata) from Okinawa Island - Ehara, Shôzô; Ueckermann, E. A. (Zootaxa, 2006)
A new genus and species, Gymnostigmaeus akaminei Ehara & Ueckermann, is described and illustrated from specimens collected on the lawngrass Zoysia tenuifolia (Poaceae) on Okinawa Island, Japan. This genus is distinct from any other known genera of the family Stigmaeidae in lacking shields and platelets on the idiosomal dorsum and venter. It is also characterized by an empodium that arises from the tip of a swollen arolium anterior to the claw bases.